Exclusive quality - Cédric Argenton (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
It is shown in this study that in the case of vertically differentiated products, Bertrand competition at the retail level does not prevent an incumbent upstream firm from using exclusivity contracts to deter the entry of a more efficient rival, contrary to what happens in the homogenous product case. Indeed, because of differentiation, the incumbent's inferior product is not eliminated upon entry. As a result, a retailer who considers rejecting the exclusivity clause expects to earn much less than the incumbent's monopoly rents. Thus, in equilibrium, the incumbent can always offer high enough an upfront payment to induce all retailers to sign on the contract.
Keywords: L12; L42; 330; vertical differentiation; contracts; exclusion; monopolization; Produktdifferenzierung; Markteintritt; Preiswettbewerb; Duopol; Vertikale Konzentration; Theorie